Daytime sleepiness related to sleep quality and perceived symptoms among undergraduate students in university / Mardhiah Kamaruddin, Ain Farhana Abdul Halim, and Wan Nor Anis Marini Wan Mohd Saidi - Kamaruddin, Mardhiah; Abdul Halim, Ain Farhana; Wan Mohd Saidi, Wan Nor Anis Marini (2015)
Background: Daytime sleepiness is the most common problem affecting these students in relation to the sleep quality measured, which is always portrayed during morning classes. It is understood that undergraduate students are experiencing excessive daytime sleepiness, along with the presence of much lower quality of sleep which has becoming a major concern among health professionals, parents as well as the lecturers. Objectives: To evaluate daytime sleepiness related to sleep quality and perceived symptoms among the undergraduates in UiTM Puncak Alam campus. Method: A cross-sectional study design will be employed whereby a self-reported questionnaire will be distributed to 372 full-time undergraduate students in UiTM Puncak Alam campus. Results: 305 respondents were participating in this study where approximately 62% of the students experienced daytime sleepiness and 59.7% students were identified to be poor sleepers due to their (PSQI >5). Blurred vision was perceived the most by students. Faculties that were associated with daytime sleepiness were Health Sciences (mean = 1.49), Art and Design (mean = 1.79), Hotel (mean = 1.50) and Business Management (mean == 1.72). Meanwhile, semester 3 (mean = 13.18) and semester 4 (mean = 1.0.-96) were the- most associated semester with daytime sleepiness. The association was found to be significant between daytime sleepiness, sleep quality and perceived symptoms with r = 0.291; 0.212 Conclusion: Daytime sleepiness is prevalent among university students. Continuous research shall be conducted towards identifying more determinants affecting the prevalence. Students, the educators, educational institutions and health institutions need to incorporate current interventions toward achieving maximize efforts of combating the prevalence.